Commentaries on Price Policy and Equity - Eicher, Carl K.; Spencer, Dunstan (International Food Policy Research Institute, 1987)
Development literature illustrates the need for a broad conceptual framework that encompasses poverty, hunger, and inequality. Drawing on two decades of research in India, Mellor (1978) demonstrates the process of isolating the direct and indirect effects of food price changes on producers and consumers by income class. More recently, Timmer et al. (1983) argue that the complexity of the problems of poverty and hunger calls for integrated analyses of food production decisionmaking, food consumption and nutrition, macropolicy and planning, and comparative advantage through international trade.